Integration of Gender, Disability, and Social Inclusion Principles in Merdeka Curriculum English Textbooks - Yuliana Dg Macora; Novalita Fransisca Tungka (Universitas Sintuwu Maroso, 2025)
This study aims to explain how the interaction between images and texts constructs meanings related to gender equality, disability, and social inclusion (GEDSI) in English textbooks for Senior High School/Islamic Senior High school (SMA/MA) of the Merdeka Curriculum, for instance Life Today and Train of Thoughts. A mixed-methods explanatory sequential design was applied by combining quantitative and qualitative data. The data of GEDSI-oriented are analyzed by using Visual Grammar theory of Kress and van Leeuwen (2020). The findings reveal that the English textbooks partially reflect GEDSI principles. While the visual representations demonstrate some awareness of gender and disability inclusion. They predominantly reproduce traditional gender roles, such as female character are still more strongly associated with domestic and caregiving roles, while male characters are positioned lie outside the home, and present disability as marginal rather than integral to the narratives. As a result, although the textbooks include certain inclusive elements, their multimodal design provides only limited opportunities for senior high school students to develop a critical understanding of GEDSI-related issues.